Integrating Massive Open Online Courses into Blended Learning in Indonesian Health Sciences Education: Development and Validation of the HS-MIF Framework - Agus Riyanto; Imma Rachayu (Yayasan Sembilan Pemuda Indonesia, 2027)
This mixed-methods study examines the integration of Massive Open Online Courses (MOOCs) into blended learning at STIKes Bhakti Husada Bengkulu, Indonesia, and validates the Health Sciences MOOCs Integration Framework (HS-MIF). Using a quasi-experimental pre-test/post-test control group design, 94 third-semester Health Information Management students were assigned to experimental (n=47, MOOCs-supported blended learning) and control (n=47, conventional instruction) groups over 14 weeks. Data collection included academic achievement tests, the newly developed and validated MOOCs Learning Engagement Scale (MLES, 32 items, α=0.887), motivation questionnaires based on the ARCS model, and focus group discussions with 12 students and 5 faculty members. The experimental group demonstrated significantly higher post-test scores (M=84.7 vs 72.3; t=6.82, p<0.001, Cohen’s d=0.89), motivation scores (M=81.4 vs 69.2, p<0.001), and an exceptional 87.2% course completion rate. The HS-MIF showed strong predictive validity (R²=0.79, p<0.001), with self-regulated learning as the strongest predictor (β=0.44). Qualitative findings revealed enhanced student engagement, perceived global competency, and faculty role transformation, alongside challenges in English language proficiency and internet connectivity. These findings provide empirical evidence for the effectiveness of structured MOOCs integration in health sciences education and offer a validated framework for implementation in resource-constrained institutions in developing countries.